Identification of capsazepine as a novel inhibitor of system x(c)(−) and cancer-induced bone pain - Fazzari, Jennifer (J Pain Res, 2017)
The cystine/glutamate antiporter has been implicated in a variety of cancers as a major mediator of redox homeostasis. The excess glutamate secreted by this transporter in aggressive cancer cells has been associated with cancer-induced bone pain (CIBP) from distal breast cancer metastases. High-throughput screening of small molecule inhibitors of glutamate release from breast cancer cells identified several potential compounds. One such compound, capsazepine (CPZ), was confirmed to inhibit the functional unit of system x(c)(−) (xCT) through its ability to block uptake of its radiolabeled substrate, cystine. Blockade of this antiporter induced production of reactive oxygen species (ROS) within 4 hours and induced cell death within 48 hours at concentrations exceeding 25 μM. Furthermore, cell death and ROS production were significantly reduced by co-treatment with N-acetylcysteine, suggesting that CPZ toxicity is associated with ROS-induced cell death. These data suggest that CPZ can modulate system x(c)(−) activity in vitro and this translates into antinociception in an in vivo model of CIBP where systemic administration of CPZ successfully delayed the onset and reversed CIBP-induced nociceptive behaviors resulting from intrafemoral MDA-MB-231 tumors.